Rynek rolny, jego funkcja i rola w sterowaniu produkcją - Szulce, Halina (Wydział Prawa i Administracji UAM, 1980)
An attempt has been taken up in the elaboration to discuss achievements of Poznan centre of commercial sciences in the sphere of — widely understood — agricultural problems. Some thought directions connected with determination of effectiveness of the most important market policy instruments in shaping equilibrium of the food-stuff market, and particularly in stimulation of agricultural production level and structure have been also presented. More important research results from the sphere of agricultural products market, as well as country trade, carried on in the Poznan scientific centre in the past 30 years, have been shown.
Agricultural Market, Its Functions and Role in Production Steering